Analysis of loading profile effect on testing machine calibration results. (December 2021) - Hiti, Miha
Abstract: The paper presents an evaluation of the loading profile effect on the testing machine calibration. First, a 20 kN force transducer was calibrated in a force calibration machine. This transducer was then used for a number of calibration runs in a 600 kN material testing machine where the time step interval of the same loading profile was varied from 120 s to 0 s. Results show good agreement for most of the range but highlight an increasing error due to synchronization and filtering issues in measured signals when approaching very short step intervals and continuous loading.